Development of Single Sized Aggregate Porous Concrete for Sustainable Road in Low Traffic Area. Issue 1 (May 2021) - Setyawan, A; Suryoto; Wibowo; Rifai, M; Sumarsono, A; Handayani, F S; Qosam, O I
Abstract: Porous concrete design with selected gradation and the developed method is proven to be able to withstand light traffic loads and pass water so that rainwater can be used optimally and keep the ground surface remains a green open area. Porous Concrete is a special concrete material produced with aggregate, cement and water with high porosity, which is between 15 to 30 %, so that water can be easily to pass. The main function of porous concrete is as a concrete pavement covering the soil surface with the aim that water can easily flow under the concrete layer, and thus the excess surface water will be reabsorbed into the ground, rather than just being wasted into the sea, the method of producing porous concrete has been patented. The mixture creates an open cell structure, allowing rainwater to penetrate the underlying land. It can be used for low-traffic areas. Porous concrete that uses one size aggregate or uniform aggregate has low compressive strength but good permeability. Porous concrete at 28 days age has a compressive strength between 3 to 28 MPa with a porosity of 14 to 31 % and a permeability ranging from 0.25 to 6.1 mm / second.